2021
DOI: 10.24018/ejdent.2021.2.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oxidative Stress on Dental Implants

Abstract: Periodontal disease is an inflammatory condition that alters the periodontium, resulting in destruction of the alveolar bone; without treatment the condition may lead to tooth loss. Dental implants are an alternative for substitution of naturally lost teeth as they have high success rates; however, some factors are related to its failure. Peri-implantitis (PI) is a pathological condition that affects the tissues surrounding dental implants and has been reported as the major cause of implant failure; PI and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…After a dental implant placement, friction and twisting could damage the oxide layer on the surface, leading to an increase of ROS and an inflammatory, such as peri‐implantitis (PI) 210,211 …”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…After a dental implant placement, friction and twisting could damage the oxide layer on the surface, leading to an increase of ROS and an inflammatory, such as peri‐implantitis (PI) 210,211 …”
Section: Oxidative Stressmentioning
confidence: 99%
“…After a dental implant placement, friction and twisting could damage the oxide layer on the surface, leading to an increase of ROS and an inflammatory, such as peri-implantitis (PI). 210,211 Antioxidants are choices for treatment. PI and periodontal disease are manifested by soft tissue and bone damage, in which ROS plays an important role in cell transmission, maintenance, and proliferation.…”
Section: Clinical Evidencementioning
confidence: 99%
“…If it is not treated in time, tooth loss might be the consequence. Dental implantations are currently an effective method for the treatment of tooth loss [ 70 ]. Biomaterials used to make dental implants include metals, ceramics, carbons, polymers, and composites.…”
Section: Antioxidants Used In Dental Proceduresmentioning
confidence: 99%
“…In addition, Abdulhameed et al [ 79 ] reported that titanium dioxide nanoparticles (TiO 2 NPs) can induce oxidative stress, reduce osteogenesis, and damage the antioxidant defense system. After placement of a dental implant, friction and twisting can destroy the oxide layer on the surface, leading to an increase of ROS and an inflammatory, such as peri-implant (PI), infection may occur ( Figure 3 ) [ 70 , 80 ]. Antioxidants such as ascorbic acid, polyphenols, and vitamin E are choices for treatment.…”
Section: Antioxidants Used In Dental Proceduresmentioning
confidence: 99%
“…Nevertheless, there are limitations in EPR-CT biological experiments in terms of sensitivity, the data collection rate, the short relaxation time, a lack of perfect reliable spin probes, and sluggish data collection. Free radicals are unbalanced ions with incomplete electron shells that can cause functional changes in molecules, leading to cell damage [ 34 ]. The spectral-spatial mode of EPR visualization allows one to register the full spectrum of EPR for each pixel of the image.…”
Section: Introductionmentioning
confidence: 99%